Increased Learning Outcomes With a Mix of Learning Models Group Investigation and Problem Based Learning - Hidayah, Nur (Unversitas Negeri Malang, 2018)
This research comes from the problem of using difficult language to understand, the availability of the manual, learning model and assumption student on the economics lesson.Â The solution of these problems is the combination of the learning model GI and LBC. This type of research is a Class Action Research (CAR) located in SMK Negeri 1 Malang on grade XI PM 3. Data collection techniques are conducted through observation, cognitive tests, and documentation and field notes. Results of the study showed an increase in the results of a study of the I-cycle to cycle II with an average classical completeness 66.78 with the number of 9 students have completed and 23 are not complete. The predicate results show that approximately 85 students are categorized as not good, while 30 students complete with predicate very good and the least 2 students are under minimum criteria.